Impact of the 7E Teaching Model on Secondary School Students’ Academic Achievement in Biology in Ilorin, Nigeria - Abdulrahim, Basira Jibril (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The continuous advocacy by scholars in science education on the shift from teachers’ conventional teaching to a more innovative teaching instruction that aligns with the global teaching trends in this 21st century leads to the emergence of the learning cycle teaching model in Education. This study examined the impact of the 7E teaching model on enhancing secondary school students’ academic achievement in biology in Ilorin. A quasi-experimental design was employed, involving a sample of 226 biology students in public secondary schools in Ilorin town. A purposive sampling technique was used to select the secondary schools in the Ilorin district. Data collection was carried out using a Biology Concepts Test (BCoT). The data analysis was conducted using mean and ANCOVA. The results indicate a significant difference between the students exposed to the 7E instructional model and those taught using the conventional teaching method, leading to the rejection of the null hypothesis. It was therefore recommended, among suggestions, that Teachers should adopt the 7E model as a teaching approach in Science and Biology to enhance students' conceptual understanding and improve academic achievement.